Desigualdades socioespaciais de acesso a oportunidades nas cidades brasileiras - 2019 - Rafael H. M. Pereira; Carlos Kauê Vieira Braga; Bernardo Serra; Vanessa Gapriotti Nadalin (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– One of the core aims of transportation policies is to facilitate people's access to employment, health and education opportunities as well as cultural and leisure activities. Nonetheless, transport research and policies in Brazil are still largely focused on the challenges of reducing road congestion and commuting times, while paying little attention to issues of urban accessibility. This study presents the first results of the Access to Opportunities Project, assessing the inequalities in access to opportunities in Brazilian largest cities in 2019 with estimates of access to jobs, health and education services. In this edition, the study includes accessibility estimates by active transport modes (walking and cycling) for the 20 largest cities in the country, and by public transport for 7 major cities (Sao Paulo, Rio de Janeiro, Belo Horizonte, Recife, Fortaleza, Porto Alegre and Curitiba). The project combines data from administrative records, sample surveys, satellite imagery and collaborative mapping to calculate accessibility levels at high spatial resolution and disaggregated by socioeconomic groups according to income level and race. The results reveal two general patterns. In all the twenty analyzed cities, the concentration of activities in central urban areas combined with the performance/connectivity of transportation networks lead to areas of high accessibility close to city centers in contrast to urban peripheries marked by deserts of opportunities. Furthermore, the results show that white and high-income people have, on average, higher accessibility to employment, health and education opportunities than black and low-income people in all of the cities analyzed, regardless of transportation mode. The results and data outputs of the Access to Opportunities Project are made publicly available, creating a rich dataset that can be used to improve the planning and evaluation of public policies aimed to promote sustainable and inclusive cities.
Keywords: R4; R41; R42; R48; O18; H4; H43; 330; accessibility; equity; equality of opportunity; transport policies; public transport; urban mobility; active transport